2021
DOI: 10.3390/polym13121952
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Carbon Coatings for Total Knee Replacements—Part I: Deposition, Cytocompatibility, Chemical and Mechanical Properties

Abstract: Diamond-like carbon (DLC) coatings have the potential to reduce implant wear and thus to contribute to avoiding premature failure and increase service life of total knee replacements (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt–chromium–molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While a detailed characterization of the tribological behavior is the subject of part II, part I focuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 112 publications
2
20
0
Order By: Relevance
“…The multilayer character with the WC inter-and the Cr adhesion layers can also be seen from the EDX line scans (Figure 1c, g). The cauliflower-like topographies of both coatings pointed towards a DLC-typical and fine columnar growth [55] (Figure 1a, e). The Raman spectra 10 (Figure 1d, h) featured two distinct peaks around 1340 and 1555 cm -1 , which are characteristic for the D-and G-bands of DLC coatings [56,57].…”
Section: Coating Propertiesmentioning
confidence: 91%
“…The multilayer character with the WC inter-and the Cr adhesion layers can also be seen from the EDX line scans (Figure 1c, g). The cauliflower-like topographies of both coatings pointed towards a DLC-typical and fine columnar growth [55] (Figure 1a, e). The Raman spectra 10 (Figure 1d, h) featured two distinct peaks around 1340 and 1555 cm -1 , which are characteristic for the D-and G-bands of DLC coatings [56,57].…”
Section: Coating Propertiesmentioning
confidence: 91%
“…The investigated substrate was medical UHMWPE [34] (Chirulen ® GUR 1020, Mitsubishi Chemical Advanced Materials, Vreden, Germany). The specimens to be coated were flat disks, which have been used for mechanical characterization (see [35]). The UHMWPE disks had a diameter of 45 mm and a height of 8 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In general, increased sputtering power could increase E IT and H IT by more than a factor of three. Accordingly, the higher coating hardness is expected to shield the substrates from adhesive and abrasive wear and also to shift the cracking towards higher stresses [28,35]. At the same time, the relatively lower indentation modulus leads to an increased ability of the coatings to sag without flowing [33].…”
Section: Data Generationmentioning
confidence: 99%
“…Some researchers have prepared composite materials by adding wear-resistant additives such as hydroxyapatite, 12,13 carbon nanotubes, 14 and amorphous carbon to enhance the wear resistance. 15 However, they did not directly improve the crosslinking of the UHMWPE matrix, and they also failed to reveal the mechanism of the long-term failure of artificial joints. Other studies indicated that the longterm failure is due to the "slow release" of trapped free radicals in the crystal region, which were induced by irradiation crosslinking.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, a few efforts have been made by researchers to address the long-term failure of artificial joints made from crosslinked UHMWPE. Some researchers have prepared composite materials by adding wear-resistant additives such as hydroxyapatite, , carbon nanotubes, and amorphous carbon to enhance the wear resistance . However, they did not directly improve the crosslinking of the UHMWPE matrix, and they also failed to reveal the mechanism of the long-term failure of artificial joints.…”
Section: Introductionmentioning
confidence: 99%